2010
DOI: 10.1002/bdd.731
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor alpha increases P‐glycoprotein expression in a BME‐UV in vitro model of mammary epithelial cells

Abstract: P-glycoprotein is an efflux pump belonging to the ATP-binding cassette super-family that influences the bioavailability and disposition of many drugs. Mammary epithelial cells express various drug transporters including P-glycoprotein, albeit at low level during lactation. During inflammatory reactions, which can be associated with changes in epithelial barrier functions, pro-inflammatory cytokines such as tumor necrosis factor alpha (TNF-α) are elevated in milk and serum. In this study, the role of TNF-α in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 72 publications
1
18
0
Order By: Relevance
“…Our current data show that the cytokine IL-1␤ increases protein expression of Pgp in a fashion similar to that reported by others, in epithelial cells (18), rat astrocytes (23), a human brain endothelial cell line (6), rat brain endothelial cells (19), and isolated rat brain capillaries (20,21). This is consistent with the effects elicited by other cytokines such as TNF␣, which has been shown to increase Pgp protein and mRNA expression in a human brain endothelial cell line (6) and to increase Pgp protein expression and activity in rat brain capillaries (21).…”
Section: Fig 6 3␤-diol Inhibited Cytokine-induced Increases In Cox-supporting
confidence: 91%
See 1 more Smart Citation
“…Our current data show that the cytokine IL-1␤ increases protein expression of Pgp in a fashion similar to that reported by others, in epithelial cells (18), rat astrocytes (23), a human brain endothelial cell line (6), rat brain endothelial cells (19), and isolated rat brain capillaries (20,21). This is consistent with the effects elicited by other cytokines such as TNF␣, which has been shown to increase Pgp protein and mRNA expression in a human brain endothelial cell line (6) and to increase Pgp protein expression and activity in rat brain capillaries (21).…”
Section: Fig 6 3␤-diol Inhibited Cytokine-induced Increases In Cox-supporting
confidence: 91%
“…Studies have shown that factors that promote inflammation increase Pgp expression/activity in both human and rodent cells/ tissue (6,(18)(19)(20)(21)(22)(23). For example, the cytokine, TNF␣, has been shown to increase Pgp protein and mRNA expression in human and rat brain endothelial cell lines (6,22).…”
mentioning
confidence: 99%
“…In this context, multidrug resistance transporters such as P-glycoprotein (P-gp; encoded by Abcb1a/b genes in the mouse) and breast cancer resistance protein (BCRP; encoded by Abcg2 gene), are functionally modulated by pro-inflammatory agents in different tissues/cell types [5][10]. P-gp and BCRP are extensively expressed in different tissue barriers such as the placenta, blood-brain barrier, mammary gland, colon and small intestine [11].…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, the effect of acute inflammation on the mammary epithelial integrity has been assessed. It was shown that TNF α may decrease the flux of drugs across the mammary epithelial monolayer by upregulating the expression of P‐glycoprotein (P‐gp) during mastitis soon after the cells are exposed to this inflammatory cytokine (Al‐bataineh et al. , 2010).…”
Section: Pharmacology Of Imm Productsmentioning
confidence: 99%